Preclinical trials of distant noninvasive electromagnetic therapy for fracture recovery in rats - Kuzmina, Irina Victorovna; Galkina, Ekaterina A.; Bondarchuk, Elena Vladimirovna; Ovchinnikov, Oleg Vyacheslavovich; Turkanov, Igor Fedorovich; Gryaznov, Valery Georgievich; Vaganov, Alexey Gennadievich; Flaks, Grigory Arnoldovich; Aistova, Lyubov Germanovna (Frontiers in Veterinary Science, 2025)
ResumeTo date the injury rate is becoming an acute and significant problem. Very often, injuries are the cause of patient disability and, subsequently, have a lasting negative impact on human health. Among the various types of injuries, bone damages, including fractures of long tubular bones, deserve a special attention.PurposeThis study evaluates the effect of noninvasive distant electromagnetic therapy on fracture healing in rats.Materials and methodsThe research was performed on the basis of the Russian Federation “Scientific Research Institute of General Pathology and Pathophysiology” on 48 white nonlinear male rats in accordance with the bioethical norms of this institution and the general ethical principles of experiments with animals, consistent with the provisions of the “European Convention for the Protection of Vertebrates Used for Experimental and Other Scientific Purposes” (2003). The animals were divided into two groups. All rats underwent surgery to create a tibial fracture damage without displacement. The groups were disposed in different rooms, located at a considerable distance from each other. A distant noninvasive electromagnetic therapy device was applied for experimental animals with very weak non-ionized non-thermal pulsed electromagnetic fields (PEMF).ResultsMorpho-biochemical blood analysis had shown a decrease in the leukocytes total number, an increase in erythrocytes and platelets for all study stages in the experimental group. And also, a reliable increase in calcium ions in the blood had been detected the last week of the preclinical trials. According to the results of X-ray studies, the bone fractures in the experimental group completely healed a week earlier than in animals of the control group. While in control individuals the recovery process had required 30 days, in animals of the experimental group it had completed after 23 days. The weight gain by animals had demonstrated the general stress reaction development and pain syndrome immediately after surgery and the following gradual recovery and condition stabilization. Weight gain in the experimental group occurred to be weaker vs. the control group that, obviously, associated with a bone fusion accelerated process, which requires a large amount of energy to restore tissue.ConclusionOur data indicated a more effective course of wound recovery and bone tissue fusion after surgery with the absence of purulent abscesses under the influence of electromagnetic therapy.